VARIASI PEMBELAJARAN MATEMATIKA DI Ã¢â¬ÅSEKOLAH Ã¢â¬â RUMAHÃ¢â¬Â BAGI PARA HOMESCHOOLER - Abidin, Zaenal (Universitas Negeri Semarang, 2007)
Homeschooling is a relatively new term in the Indonesian education. TheDepartment of National Education (Depdiknas) officially introduces homeschooling as